2011
DOI: 10.1177/0887403411424081
|View full text |Cite
|
Sign up to set email alerts
|

Value Conflict and Public Opinion Toward Prisoner Reentry Initiatives

Abstract: The dramatic growth in the incarceration rate since the mid-1970s has unintentionally resulted in massive numbers of people being released from prison each year. Consequently, prisoner reentry initiatives are receiving greater attention than ever before. At this point few studies have looked at public support for reentry initiatives, and the existing ones have taken a rather general and atheoretical approach. The current study explores public opinion toward a wide range of reentry policies and practices throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 38 publications
4
71
0
Order By: Relevance
“…Reevaluations of the importance of prisoner reentry initiatives are likely driven in part by lackluster economic realities which are affecting funding and resource allocation (B. Garland et al, 2013). In addition, while the new prisoner reentry movement started with a flurry of ideas and signs of success, the impact of reentry programming is now being questioned (B.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reevaluations of the importance of prisoner reentry initiatives are likely driven in part by lackluster economic realities which are affecting funding and resource allocation (B. Garland et al, 2013). In addition, while the new prisoner reentry movement started with a flurry of ideas and signs of success, the impact of reentry programming is now being questioned (B.…”
Section: Discussionmentioning
confidence: 99%
“…A study on public opinion and prisoner reentry in Missouri similarly found support for fundamental components of reentry (B. Garland, Wodahl, & Schuhmann, 2013). For example, 89% of Missouri residents believe it is a good idea to help people coming out of prison get services, 76% felt that employment-based reentry programs should strive to get prisoners earning enough money to make a stable living, and roughly 9 out of 10 Missourians favor substance abuse and mental health programs for recently released prisoners.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, citizen opposition has frequently forced sex offenders (SOs) to live in neighborhoods considered to be socially disorganized and with few social supports (e.g., Hughes and Burchfield, ; Hughes and Kadleck, ; Socia and Stamatel, ; Tewksbury and Mustaine, , ). Researchers have found that citizens also strongly oppose housing drug and violent offenders in their cities and neighborhoods (Garland, Wodahl, and Schuhmann, ). Furthermore, landlords are hesitant to rent to those with criminal records (Israelsen‐Hartley, ).…”
mentioning
confidence: 99%
“…However, this global support should not be seen as a blank check. Thus, in their Missouri survey, Garland, Wodahl, and Schuhmann (2013) found that support for reentry programs diminished when the respondents were asked to raise taxes to pay for them or to give ex-offenders preference for services over nonoffenders. These data should not be taken as evidence that the public's endorsement of reentry is soft.…”
Section: A Decade Latermentioning
confidence: 93%